STRATEGIC GUIDELINES FOR THE DEVELOPMENT OF AN INFORMATION SUPPORT SYSTEM FOR AGRICULTURAL ENTERPRISE MANAGEMENT - Vakulenko, Vitalii; Gorgo, Iryna; Voskolupov, Volodymyr; Liu, Yuntao; Liu, Xiaowei (Current Problems of Sustainable Development, 2026)
The article provides a comprehensive exploration of the strategic role of modern information support systems in enhancing the efficiency, adaptability, and strategic sustainability of agricultural enterprise management in Ukraine. It substantiates the conceptual foundations and developmental imperatives of such systems within the context of digital transformation, economic turbulence, and intensifying global competition. The information support system is conceptualized as an integral component of the management architecture that enables the continuous acquisition, processing, and interpretation of multidimensional data to ensure informed, evidence-based, and timely managerial decision-making across all functional levels of agricultural enterprises. The study identifies the modernization of hardware and software infrastructures, the integration of advanced digital tools and analytical platforms, the enhancement of digital competencies among personnel, and the establishment of robust cybersecurity mechanisms as key strategic orientations for the evolution of the information support system. The adoption of cutting-edge digital technologies – including cloud computing, the Internet of Things (IoT), artificial intelligence, and Big Data analytics – is shown to provide comprehensive support for management functions, optimize production, logistics, and financial flows, and increase the precision of planning and responsiveness to market dynamics, environmental variability, and climatic risks. It is argued that the development of an intelligent and adaptive information support system transforms traditional management processes into a data-driven, strategically coordinated framework capable of anticipating changes and mitigating operational and strategic risks. Such transformation fosters managerial agility, enhances organizational resilience, and reinforces the competitiveness of agricultural enterprises within the paradigm of sustainable and innovation-oriented growth. The findings enrich the theoretical and methodological foundations of agrarian management science and offer practical recommendations for the strategic digitalization of decision-making processes, thereby contributing to the formation of a resilient, knowledge-intensive, and globally competitive agricultural sector in Ukraine.
Keywords: agricultural enterprises; information support; management; information support system; strategic guidelines